The Implementation Of Differentiation Strategies In English Classes - Muxsinova Kumushxon Suhrob Qizi (Euro Asian Journal Publishing, 2024)
The Article Deals With An Approach To Teaching Called Differentiation As Creating A Balance Between Academic Content And Students’ Individual Needs. In The Article, The Author Focuses On Describing What Differentiation Is And Providing The Reasons For The Use Of Differentiated Strategies. The Author Highlights The Importance Of Making A Differentiated Lesson, Where A Teacher Will Be Able To Create Different Ways Of Learning The Educational Content. The Teacher Also Designs Multiple Ways Students Can Create A Product To Prove That They Have Learned The Material. The Author Mentions That At A Traditional Lesson The Same Material Is Taught Only Through One Process Ending With The Same Product For Everyone In The Class. For Example, In Many Classes The Students Come To The Lesson And Listen To The Teachers’ Lecture About Some Topic. Then They Take Tests And Leave. The Next Day The Same Thing Happens. The Author Highlights That At A Differentiated Lesson, The Teacher Creates Different Versions Of The Same Lesson To Meet The Needs And Skills Of All Students, From The Most Challenged To The Most Gifted Ones.
Keywords: Implementation; Differentiation Strategies; English Classes